Impact of the employment and unemployment level on the use of flexible forms of employment in EU countries - Zieliński, Mariusz (Wpływ poziomu zatrudnienia i bezrobocia na wykorzystanie elastycznych form zatrudnienia w krajach UE, 2019)
The aim of the article is to examine the correlation between changes in the level of employment and unemployment rate and the share of non-standard (flexible) forms of employment in the countries of the European Union in the long-term perspective. The hypothesis is that changes in the employment level and unemployment rate are related to the changes in the share of non-standard forms of employment in overall employment. The assessment of the relationship between the studied values refers to the age group of between 15 and 64-year olds. Coefficients of linear correlation and determination between the studied values in 2006-2017 were calculated in order to verify the hypothesis. The results of the research indicate that the situation is very different in different national labour markets, both in terms of the share of nonstandard forms of employment and their reactions to changes in employment and unemployment
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2019; vol. 63, nr 6, s. 127-136
Keywords: non-standard forms of employment; level of employment; unemployment rate; European Union; elastyczne formy zatrudnienia; stopa bezrobocia; poziom zatrudnienia; Unia Europejska